2016
DOI: 10.1177/1535370216647127
|View full text |Cite
|
Sign up to set email alerts
|

The use of engineered protein materials in electrochemical devices

Abstract: Bioelectrochemical technologies have an important and growing role in healthcare, with applications in sensing and diagnostics, as well as the potential to be used as implantable power sources and be integrated with automated drug delivery systems. Challenges associated with enzyme-based electrodes include low current density and short functional lifetimes. Protein engineering is emerging as a powerful tool to overcome these issues. By taking advantage of the ability to precisely define protein sequences, elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Shorter chains containing less than 50 amino acids are called peptides. Polypeptide engineering is the process of developing polypeptides for a specific valuable function, and has resulted the development of new biomaterials, 71 drug-delivery platforms, 72,73 therapeutics, 74 antimicrobial agents, 75 nanomaterials, 76 hydrogels, 77,78 electrochemical systems, 79 sensors, 80 and superior biocatalysts. 81,82 Benefits of polypeptide engineering include the ability to specifically and easily define and tune the sequence of amino acids in a polypeptide chain, where in addition to natural amino acids, unnatural amino acids can also be incorporated into the sequence, expanding the available design space.…”
Section: Peptide and Polypeptide Engineering And Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Shorter chains containing less than 50 amino acids are called peptides. Polypeptide engineering is the process of developing polypeptides for a specific valuable function, and has resulted the development of new biomaterials, 71 drug-delivery platforms, 72,73 therapeutics, 74 antimicrobial agents, 75 nanomaterials, 76 hydrogels, 77,78 electrochemical systems, 79 sensors, 80 and superior biocatalysts. 81,82 Benefits of polypeptide engineering include the ability to specifically and easily define and tune the sequence of amino acids in a polypeptide chain, where in addition to natural amino acids, unnatural amino acids can also be incorporated into the sequence, expanding the available design space.…”
Section: Peptide and Polypeptide Engineering And Designmentioning
confidence: 99%
“…Shorter chains containing less than 50 amino acids are called peptides. Polypeptide engineering is the process of developing polypeptides for a specific valuable function, and has resulted the development of new biomaterials, drug-delivery platforms, , therapeutics, antimicrobial agents, nanomaterials, hydrogels, , electrochemical systems, sensors, and superior biocatalysts. , Benefits of polypeptide engineering include the ability to specifically and easily define and tune the sequence of amino acids in a polypeptide chain, where in addition to natural amino acids, unnatural amino acids can also be incorporated into the sequence, expanding the available design space. , Other benefits of polypeptide engineering include biocompatibility as well the ability to design multiple functions and stimuli-responsiveness into the molecules. Polypeptides are also easy to manufacture using established molecular biology techniques where the DNA of a host organism is strategically manipulated such that the organism will produce the polypeptide of interest.…”
Section: Designing Peptides and Polypeptidesmentioning
confidence: 99%
“…It has been suggested that surfaces, such as the inside of the chaperonin cavity, alter the free energy landscape of folding, preventing misfolded intermediates, and full atomistic simulations of such large systems have only recently become accessible . Third, from an application perspective, the growing interest in immobilizing proteins on abiological surfaces for use in biosensors and catalytic devices likewise will require accurate simulations of the biomolecular structure and dynamics within these artificial environments to develop and test hypotheses of protein–surface interactions. Evolved biological molecules offer specificity and reactivity that have yet to be replicated in artificial devices and could therefore be of enormous benefit to the biomedical community if they could be reliably incorporated into artificial materials. The glucose monitor, which converts blood glucose concentration to an electrochemical readout using glucose oxidase bound to a biochemical sensor, is a well-known example of such a device .…”
Section: Introductionmentioning
confidence: 99%